Utilizing Residents' Houses as Homestays to Support Historical Tourism Trowulan Village, Mojokerto, East Java - Suriani, Nuremma; Reindrawati, Dian Yulie; Nuruddin; Wirawan, Putu Eka (Jurnal Ilmiah Hospitality Management, 2025)
ABSTRAK Trowulan Tourism Village in Mojokerto Regency, East Java, is a historical tourism destination, a historical area relics of the Majapahit Kingdom. The high level of tourist interest in the village's cultural and archaeological sites demands accommodations that are not only adequate but also capable of providing an authentic experience. This study aims to examine the potential of utilizing residents' homes as homestays to support the development of community-based historical tourism in Trowulan Village, Mojokerto. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. The results show that the community is enthusiastic and aware of the potential of homestays to improve the local economy and preserve culture. However, several challenges remain, such as limited housing infrastructure, lack of training in homestay management, and concerns about cultural differences and security. Therefore, support from the government and stakeholders is needed to provide training, mentoring, and assistance with facility improvements so that homestays can develop optimally and sustainably.